Enhanced memory for context associated with corrective feedback: evidence for episodic processes in errorful learning. Issue 8 (14th September 2021) - Overman, Amy A.; Stephens, Joseph D. W.; Bernhardt, Mary F.
ABSTRACT: Numerous studies have established that there are benefits of corrective feedback for learning, but the mechanisms of this benefit are not well understood. An important question is whether corrective feedback improves memory via episodic processes or solely via semantic mediation. If episodic processes are involved, then memory for corrective feedback should include contextual details of the feedback episode. The present study tested this hypothesis across 3 experiments (total n = 223) in which participants completed an encoding task that involved cued guessing of category exemplars. Exemplars generated by participants were equally likely to be treated as correct or incorrect, and the "correct" exemplar was presented within a feedback display after each response. Separate versions of the task manipulated font colour in either the feedback display or the initial cue/typed response display. Participants were instructed to remember either the correct exemplars or their own typed responses, and the corresponding font colours. Retrieval task (cued recall, free recall, recognition) was varied across experiments. Across all 3 experiments, a higher rate of memory accuracy was observed for context associated with corrective feedback relative to other conditions. The findings are consistent with the hypothesis that errorful learning involves episodic memory, not merely semantic mediation.